Association between jail‐based methadone or buprenorphine treatment for opioid use disorder and overdose mortality after release from New York City jails 2011–17. (16th November 2022) - Lim, Sungwoo; Cherian, Teena; Katyal, Monica; Goldfeld, Keith S.; McDonald, Ryan; Wiewel, Ellen; Khan, Maria; Krawczyk, Noa; Braunstein, Sarah; Murphy, Sean M.; Jalali, Ali; Jeng, Philip J.; et al.
Abstract: Background and aims: Opioid overdose is a leading cause of death during the immediate time after release from jail or prison. Most jails in the United States do not provide methadone and buprenorphine treatment for opioid use disorder (MOUD), and research in estimating its impact in jail settings is limited. We aimed to test the hypothesis that in‐jail MOUD is associated with lower overdose mortality risk post‐release. Design, setting and participants: Retrospective, observational cohort study of 15 797 adults with opioid use disorder who were released from New York City jails to the community in 2011–2017. They experienced 31 382 incarcerations and were followed up to 1 year. Measurements: The primary outcomes were death caused by accidental drug poisoning and all‐cause death. The exposure was receipt of MOUD (17 119 events) versus out‐of‐treatment (14 263 events) during the last 3 days before community re‐entry. Covariates included demographic, clinical, behavioral, housing, health‐care utilization and legal characteristics variables. We performed a multivariable, mixed‐effect Cox regression analysis to test association between in‐jail MOUD and deaths. Findings: The majority were male (82%) and their average age was 42 years. Receiving MOUD was associated with misdemeanor charges, being female, injection drug use and homelessness. During 1 year post‐release, 111 overdose deaths occurred and crude death rates were 0.49 and 0.83 per 100 person‐years for in‐jail MOUD and out‐of‐treatment groups, respectively. Accounting for confounding and random effects, in‐jail MOUD was associated with lower overdose mortality risk [adjusted hazard ratio (aHR) = 0.20, 95% confidence interval (CI) = 0.08–0.46] and all‐cause mortality risk (aHR = 0.22, 95% CI = 0.11–0.42) for the first month post‐release. Conclusions: Methadone and buprenorphine treatment for opioid use disorder during incarceration was associated with an 80% reduction in overdose mortality risk for the first month post‐release.